Associação entre o tempo de uso de mídias eletrônicas e problemas externalizantes em escolares durante a pandemia da COVID-19 - Oliveira, Katia Fernandes de (2020)
The use of electronic media, such as smartphones and tablets, has increased among children over the years, which has expanded the performance of studies seeking to understand the relationship of this use with behavioral problems. The results indicate that the massive use of media directly and indirectly impacts children's behaviors, with certain media being associated with externalizing problems, such as: aggressiveness, impulsivity, attention problems and antisocial behavior. Few studies have been carried out with samples of Brazilian children. In addition, little is known about the relationship between the use of electronic media and behavior problems during the COVID-19 pandemic, a period in which social isolation was proposed as a contention measure and electronics became the main tool school activities and social contact. Thus, this study aimed to verify the association between the time of using different types of electronic media and externalizing problems in children aged 7 to 11 years during the COVID-19 pandemic in Brazil in the evaluation of parents / guardians. The sample consisted of 277 participants (93.9% mothers), with 143 responsible for boys (mean age = 8.99 years - standard deviation = 1.36) and 134 for girls (mean age = 9.02 years - deviation default = 1.41). The instruments used were: (1) sociodemographic data sheet; (2) media activities form-parent; achenbach (2018); (3) child behavior checklist - CBCL / 6-18; Achenbach & Rescorla (2001). The link for filling out the form was posted on social networks, as well as through WhatsApp messages for potential participants from 10/06/2020 to 8/10/2020. It was found that the association between time of using electronic media and externalizing problems is present in both sexes, with a higher prevalence in girls. The association was significant and positive for: violent video games and online games in general; YouTube (used passively); creation of content for YouTube, blogs, etc; Radio, MP3, Spotify etc.; sites for fun or information. However, when the use of electronic media was for study or work, the associations were negative, indicating that children who spend more time doing such activity are those who have less externalizing problems. The fact that the study is correlational does not allow the directionality of this relationship to be inferred, that is, we cannot say that the longer use of electronics causes externalizing problems, or vice versa. However, it is essential that parents or caregivers be aware of the time spent using electronic media, as well as the content viewed or used.